Pemberdayaan Perempuan Melalui Budidaya Akuaponik Dan Pengolahan Hasil Perikanan Dalam Kegiatan Pekarangan Pangan Lestari Masyarakat Dusun Pringtali Desa Jogonegoro Kabupaten Magelang - Andri (Indonesia), Andri Nofreeana; (Indonesia), Waluyo (Fakultas Pertanian_Universitas Tidar, 2024)
Based on data collected by the Magelang Regency Livestock and Fisheries Service, in 2021 the average consumption of fishery products will reach 25,000 tons and caught fish will reach 300 tons (Tribun Jogja, 2022). This data is inversely related to the level of fish consumption in Magelang Regency. The level of fish consumption needs to be increased because it greatly affects health and nutritional intake, especially for children and the elderly. Based on this data, efforts are needed to increase fish consumption. One of them is that the use of the yard can be optimized to meet daily food needs, or what is often called sustainable food. The application method given in the field is by providing training to the women of Pringtali hamlet Rt 04/Rw 02 and Rt 03/Rw 02. The training consisted of aquaponic cultivation techniques and making cultivated fish samosas. Based on the results of the service, it can be concluded that all participants stated that they liked and were interested in taking part in training activities, being able to make or take part in training on aquaponic cultivation, and making catfish samosas, participants stated that the material presented by the presenting team or presenters was clear. The resulting output was the formation of 5 family groups that implemented aquaponics and catfish cultivation.